Moral Aspects of Some Combat Sports - Meller, Jacek (Studia Ecologiae et Bioethicae, 2020)
Nowadays, sport is very popular as a way of spending free time, taking care of one’s health and physical condition, as well as being an entertainment worth watching; sport is also judged positively, when it comes to moral aspects. However, there are disciplines that may cause doubts, because of the possible risk for the contestants (e.g. extreme sports), especially combat sports. The purpose of this article is to present an ethical analysis of full-contact combat disciplines. Their history shows a process of gradual brutalisation, in antiquity from battles during the Greek Olympics, to competitions in Roman arenas; in the modern age from regulations introduced in the 19th century and the beginning of the 20th century, to formation or restoration of combat, where almost no rules exist. Rules that apply in modern combat sports, lead to aggressive behaviour towards rivals, and give an advantage to the person who, not only strikes more technically correct blows or uses grips, but also reduces the opponent’s ability to fight further. It leads to serious injuries whose consequences remain until the end of a contestant’s life and make him a disabled person as time passes. Aggression that seriously harms a contestant, makes it impossible to morally excuse those sports.